A prospective cohort study of racial/ethnic variation in the association between change in cystatin C and dietary quality in older Americans. Issue 2 (11th April 2022) - Bishop, Nicholas J.; Zhu, Jie
Abstract: Using a sample of US adults aged 65 years and older, we examined the role of dietary quality in cystatin C change over 4 years and whether this association varied by race/ethnicity. The Health and Retirement Study provided observations with biomarkers collected in 2012 and 2016, participant attributes measured in 2012, and dietary intake assessed in 2013. The sample was restricted to respondents who were non-Hispanic/Latino White ( n 789), non-Hispanic/Latino Black ( n 108) or Hispanic/Latino ( n 61). Serum cystatin C was constructed to be equivalent to the 1999–2002 National Health and Nutrition Examination Survey (NHANES) scale. Dietary intake was assessed by a semi-quantitative FFQ with diet quality measured using an energy-adjusted form of the Alternative Healthy Eating Index-2010 (AHEI-2010). Statistical analyses were conducted using autoregressive linear modelling adjusting for covariates and complex sampling design. Cystatin C slightly increased from 1·2 mg/l to 1·3 mg/l over the observational period. Greater energy-adjusted AHEI-2010 scores were associated with slower increase in cystatin C from 2012 to 2016. Among respondents reporting moderately low to low dietary quality, Hispanic/Latinos had significantly slower increases in cystatin C than their non-Hispanic/Latino White counterparts. Our results speak to the importance of considering racial/ethnic determinants of dietary intake and subsequent changes in health in ageing populations. Further work is needed to address measurement issues including further validation of dietary intake questionnaires in diverse samples of older adults.